2017
DOI: 10.1016/j.pneurobio.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial function in hypoxic ischemic injury and influence of aging

Abstract: Mitochondria are a major target in hypoxic/ischemic injury. Mitochondrial impairment increases with age leading to dysregulation of molecular pathways linked to mitochondria. The perturbation of mitochondrial homeostasis and cellular energetics worsens outcome following hypoxic-ischemic insults in elderly individuals. In response to acute injury conditions, cellular machinery relies on rapid adaptations by modulating posttranslational modifications. Therefore, post-translational regulation of molecular mediato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
218
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 282 publications
(220 citation statements)
references
References 460 publications
(554 reference statements)
2
218
0
Order By: Relevance
“…Mitochondria are a major target in hypoxic/ischemic injury and play critical functions in the response to hypoxia, ischemia and reperfusion (Nanayakkara et al, 2015; Ham and Raju, 2016). Perturbation of mitochondrial homeostasis and cellular energetics worsens the outcome following hypoxic-ischemic insults (Nanayakkara et al, 2015; García-Rivas and Torre-Amione, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are a major target in hypoxic/ischemic injury and play critical functions in the response to hypoxia, ischemia and reperfusion (Nanayakkara et al, 2015; Ham and Raju, 2016). Perturbation of mitochondrial homeostasis and cellular energetics worsens the outcome following hypoxic-ischemic insults (Nanayakkara et al, 2015; García-Rivas and Torre-Amione, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies demonstrated a significant increase in the plasma levels of cytokines such as IL-6, TNF-α and IL-10 and activation of NF-κb (34). The hypoxic response of the host is complex as reduced oxygen availability can lead to altered mitochondrial energy metabolism as well as an inflammatory trigger (35, 36). The spleen is an organ that is important in both adaptive and innate immunity (37) and the hypoxic effect of HI on mitochondrial respiration in splenocytes has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was shown resveratrol has protective effect against cardiotoxicity induced by doxorubicin such as reduction in tissue damage and serum cardiac enzyme activities, preserving mitochondrial morphology and inherent anti-oxidant capacity [14]. Furthermore, the neuroprotective effects of resveratrol have been demonstrated in several in vitro and in vivo models of AD [15], which may be linked either directly or indirectly to protection against mitochondrial dysfunction in aging [16].…”
Section: Introductionmentioning
confidence: 99%